China's Participation in UN Peacekeeping Operations since the 2000s. Issue 117 (4th May 2019) - Cho, Sunghee
ABSTRACT: Although China's active participation in United Nations (UN) Peacekeeping Operations as a personnel contributor has drawn people's attention, very few have examined under what conditions China sent its personnel in general. This article analyzes 18 cases of China's participation/nonparticipation during 2003–2017, using such data as UN resolutions, data on trade and security, and other states' involvement. It reveals that the consideration of economic interests is a better predictor for China's behavior than China's concerns over its reputation, the insecurity of places, or mission characteristics. However, in contrast to popular speculations, economic interests are more about the importance of host states as export markets rather than as exporters of resource-related materials. The study also finds that sovereignty issues still wield power over China's decisions, showing that despite its increasing lenient voting patterns on mission resolutions, its participation behavior tends to remain conservative.